Elsa 2016 Cohort: Association between early alcohol, tobacco, or marijuana use and substance use in Argentinean college freshmen - Quiroga, Facundo (2019)
Earlier alcohol, tobacco, or marijuana consumption is associated with a greater risk of developing drug-related problems, including substance use disorders. Some authors have postulated that this risk is substance-specific (i.e., early alcohol use leads to alcohol- but not marijuana-related problems). Other authors have suggested a broader effect, in which the initiation of use of any substance (e.g., alcohol or tobacco) heightens the risk of using these and other psychoactive substances. The present study examined, in a large sample (n = 4083; 40.1% men; mean age = 19.39 ± 2.18 years) of Argentinean college freshmen, the association between age of onset (early, late) of alcohol, tobacco, and marijuana use and different indicators of substance use. Participants completed a survey that measured age of onset of alcohol, tobacco and marijuana use and different indicators of use (for each substance). The effect of age of first use on substance use was analyzed separately for each substance using the χ2 test or Student's t-test for nominal and continuous dependent variables, respectively. These analyses were conducted in the subsample that had reported lifetime use of each substance. Results: Overall, results showed that the onset of alcohol use preceded the use of tobacco, which, in turn, preceded the use of marijuana. We identified substance-specific associations: early use of alcohol, tobacco, and marijuana was associated with a higher likelihood of consuming each of these substances. Despite this, an early drinking onset was significantly associated with a reater occurrence of all indicators of tobacco and marijuana use. Moreover, the effect sizes of the associations between early drinking onset and subsequent use of all three substances were larger than the effect of early tobacco or marihuana use on subsequent use of these substances. Discussion: Altogether, our findings suggested that alcohol was the entry-point substance for the majority of the participants and a broader effect of alcohol initiation that heightens the risk of consuming alcohol and using other substances. The findings suggest that programs directed toward delaying the onset of alcohol use may be particularly useful among these individuals.